Akuntabilitas Pengelolaan Keuangan Desa Di Kecamatan Kapuas Ditinjau dari Evaluasi Penerapan Aplikasi Sistem Keuangan Desa (Siskeudes) - Willy Tri Hardianto; Fetrushio Finambello TM; Muhamad Rifa’i (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2021)
This research was conducted to determine the impact of using the SISKEUDES application in realizing the accountability of village financial management in Kapuas District. This research was conducted in the village government in the Kapuas District, Sanggau District using descriptive qualitative research methods. The technique of determining informants uses purposive sampling and uses data analysis techniques in the form of data reduction, data presentation and drawing conclusions. The results showed that the application of the SISKEUDES application to manage village finances in the village government in Kapuas District was good because it simplified the accountability reporting process and provided quality and accountable financial management reporting results with the supporting factors for implementing the application, namely infrastructure, good cooperation between warriors. villages, and the inhibiting factors are limited human resources, the capacity of the facilities used, the application is still error-prone and not online-based, while the evaluation model used in this research is Daniel Stufflebeam's CIPP (Context, Input, Process, and Product) evaluation model